The noun phrase and its translation in the novel “Budha, a story of enlightenment” - I Made Juliarta (English, 2021)
The paper analyzes the form of the noun phrase and its translation shift found in the novel “Budha, A Story of Enlightenment”. The shift in translation is stated as a major concept in a sentence analysis found in translation. The concept of shifting can be used in order to learn how a unit on a different level used to make interesting structures. This study has used the theory that is proposed by Catford (1978) and Quirk et all(1985). The qualitative method is applied to the research method by the researcher. In the data of noun phrases, it consists of the derived noun as head in the source language. In the translation process in this study, a shift occurred in the translation process from the source language into the target language. It can be seen that this study focuses on the translation strategies of the noun phrase. Those can be dictated by the structural discrepancies that occurred between the two language systems involved in this process. The optional ones (those that are dictated by the personal and stylistic preferences) and communicative rendition in source language text into another language. There are some shifts in translation occurred in the English noun phrases that are also translated into noun phrases in Indonesian as the target language. This study intends to: (i) identify the types of the noun phrase and its constituent structure found in the data source, (ii) analyze the types of translation shifts of the noun phrase in the translation process from the source language into the target language.